The adverse effect of air pollution on the pathogenesis of autism spectrum in a sample of Iraqi children - Abdullah, Sara; Al- Garawi, Zahraa; Al- Aasmi, Basim (Journal of medical and pharmaceutical sciences, 2020)
Autism is a brain disorder occurs in children during the first three years leads to poor social interactions or communication. There are few studies showed a strong relationship between exposure to air pollutants and increased risk and development of autism. We aimed here to study the impact of air pollutants on moderate autism spectrum disorder in a sample of Iraqi children living in the capital Baghdad by following up the air quality in different areas in Baghdad through measuring the concentration of air pollutants carbon monoxide، carbon dioxide، nitrogen dioxide، sulfur dioxide، ozone، total suspended micro- particles and MP10 during 2017- 2018 and compare the levels with standard levels of air pollutants. Accordingly، we selected a sample of children diagnosed with autism (n=25، school-age children، 4- 10 years old) who are living in the area of high pollutants and studied the sources of pollution closest to the residential area of children. The psychological integration of these children was diagnosed. All results compared with a sample of healthy children of the same age. The air quality results indicated higher pollution in Al- Waziriya neighborhood than other neighborhoods، represented by an increase in the concentration of pollutants. The results also showed that autistic children lived close to several sources of pollution، such as a bakery، a gas station، an industrial factory، a waste incinerator or energy generators. A percent of 80% of the children under study were moderate autistic children، however, 20% of autistic children had severe autism; the continuous exposure to these pollutants may be a cause of exacerbation. The residential area of healthy children was significantly free from those sources of pollution، 0.0001 0.0000. The autistic children have a significant lack of sensory and psychological integration when compare with healthy children 0.0001 0.00001. To sum up، neighborhoods in Baghdad have different air quality ratios، but Al- Waziriya district showed a rise in pollutant concentrations more than other neighborhoods، which may negatively affect autism spectrum disorder and lead to develop into severe autism. Therefore، the study recommends protecting autistic children or pregnant mothers from continuous and direct exposure to sources of pollution.